Ways of worldmaking : Ben Rivers. - Steinbrügge, Bettina; Camden Arts Centre; Kunstverein in Hamburg; University of Chicago. Renaissance Society; Fondazione La Triennale di Milano (Milano : Mousse Publishing, 2016)
"Ways of Worldmaking is the first comprehensive monograph on British experimental filmmaker Ben Rivers (born 1972). In recent years, Rivers has been celebrated as one of the most important experimental filmmakers of his generation. The series of exhibitions collected in this book explore the diversity and breadth of his work. Often following people who have in some way separated themselves from society, the raw film footage provides Rivers with a starting point for creating oblique narratives imagining alternative existences in marginal worlds."--Publisher's website.
Ben Rivers : ways of worldmaking / Ed Halter -- Fable / Robert Pinget -- Ah, liberty! : transcript -- In the land of the auteurs / Melissa Gronlund -- Somerset / Mark von Schlegell -- A world rattled of habit : transcript -- The green child / Herbert Read -- Origin of the species : transcript -- The creation as we saw it : transcript -- Edgelands / Renee Gladman -- I know where I'm going / Jan Zalasiewicz -- To and from elsewhere : dislocated suspension and time warping in the work of Ben River / Andréa Picard -- I am writing to you from a far-off country / Henri Michaux.
"This publication is a result of the collaboration between four different institutions who all have presented discrete solo exhibitions by Ben Rivers."--Foreword.
"Published by Camden Arts Centre, Kunstverein in Hamburg, The Renaissance Society at the University of Chicago, La Triennale di Milano"--Colophon.
boek
Keywords: Rivers, Ben, -- 1972- -- Criticism and interpretation